Improvement of Administrative Legislation Regulating the Interaction of the National Anti-Corruption Bureau of Ukraine with Other Law Enforcement Agencies (Law and Safety, 2019)
On the basis of working out the current legislation of Ukraine and a number of scientific views of scholars the author of the article defined and characterized certain directions of improvement of administrative legislation regulating interaction of the National Anti-Corruption Bureau of Ukraine with other law enforcement agencies.It is argued that the legislation is the basis of anti-corruption activities of the state and the key to its effective implementation, however, the legal framework in this field suffers from a significant load of declaratory norms that set principles and tendencies, but do not provide information on how the data principles and tendencies must be implemented.It is found out that administrative legislation regulating the interaction of the National Anti-Corruption Bureau of Ukraine with other law enforcement agencies is the system of normative and legal acts of administrative branch regulating the procedure, sequence, format and other administrative features of the interaction of NABU with law enforcement agencies.It is established that NABU's interaction with law enforcement agencies is a large, complex direction of our state's anti-corruption component, which requires defining the goals, principles, directions and levels of interaction at the legislative level. Thus, interaction, as a form of work, needs to be broadly defined at the level of legislation not within the limits of several norms, but to give this topic a separate section of the Law of Ukraine “On the National Anti-Corruption Bureau of Ukraine”. This will create a legislative guarantee for NABU's interaction with law enforcement agencies, consolidate it as an integral and necessary aspect of anti-corruption activities.It is emphasized that the by-law regulatory framework for the implementation of the relevant interaction is currently rather small in volume, so that the potential of cooperation between NABU and other law enforcement agencies cannot be disclosed, since it actually has no basis for its implementation. In this regard, it is most appropriate to consolidate the mechanisms of the Bureau's interaction with the state law enforcement agencies by extending the range of joint orders.
Keywords: improvement; administrative legislation; interaction; law enforcement; anti-corruption